HUBUNGAN FAKTOR SOSIAL EKONOMI KELUARGA, POLA KONSUMSI PANGAN DAN RIWAYAT PENYAKIT INFEKSI DENGAN KEJADIAN KURANG ENERGI KRONIS PADA IBU HAMIL DI KECAMATAN OEBOBO KOTA KUPANG - anastasia tri astuti (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2019)
ABSTRACT BackgroundChronic energy deficiency (CED) in pregnancy has been widely known to have a negative impact on the mother and the fetus it contains. The most prominent negative impact is the increased risk of maternal and infant deaths during childbirth. CED in pregnant women can be caused by an imbalance of nutritional intake and infectious diseases. The aim of this research is to know and analyze the correlation between family socioeconomic factors (age, education, occupation, income, number of family members, family support), food consumption pattern (food type, food quantity, feeding frequency, food prohibition) and history of infectious diseases CED events in pregnant women. Research methodsThe type of research used is observational analytic research with cross sectional design. Sampling in total sampling with a sample size of 72 respondents. The instrument used is questionnaire and 24 hour food recall format. Data analysis was done in three stages: univariate analysis, bivariate analysis with chi square analysis method, multivariate analysis with multiple logistic regression analysis method. ResultsThe results of the study based on bivariate analysis showed that the variables associated with CED occurrence in pregnant women were education with p = 0,001 (p <0,05), job with p value = 0,000 (p <0,05), income with p value = 0,000 (P <0,05), p = 0,000 (p <0,05), p = 0,000 (p <0,05), food consumption with p = 0,000 (p <0,05) , 05), and feeding frequency with value p = 0,008 (p <0,05). Multivariate analysis showed that variables associated with CED occurrence in pregnant women were job variable with p value = 0,026. ConclusionThere is a significant correlation between family socioeconomic factors (education, occupation, income, family support) and food consumption pattern (type of food, amount of food consumption and frequency of eating) with CED occurrence in pregnant women. Simultaneously then there is one variable that has a significant relationship with CED occurrence in pregnant women that is work.